Assessment of lower urinary tract symptoms 6 weeks after delivery and the relationship of pelvic floor muscle function - Lei Zhang; Xiaoxiao Wang; Xinnan Hou; Xinrong Zhuang; Yu Wang; Xiaoqing Wang; Ye Lu (Frontiers Media S.A., 2024)
BackgroundStudies on lower urinary tract symptoms (LUTS) in women, especially in relation to different modes of delivery, are limited. The relationship between the emergence of LUTS and the decline of pelvic muscle function after childbirth remains uncertain.Study designThis observational study was carried out at the Peking University First Hospital over a time span of 2019-2022. A total of 2,462 women were recruited and surveyed 6 weeks after delivery, utilizing questionnaires for data collection. Additionally, gynecological physical examinations and pelvic floor muscle screenings were conducted as part of the study. To assess individual LUTS and the level of discomfort caused by these symptoms, a modified Chinese version of the Bristol Female Lower Urinary Tract Symptoms questionnaire was employed. Data analysis methods such as descriptive statistics, χ2 tests, one-way ANOVAs, and multivariate logistic regressions were used to thoroughly examine the collected data.ResultsA high prevalence of LUTS was observed in the study participants, with 70.6% experiencing any symptoms. Storage symptoms were reported by 65.4%, while voiding symptoms were reported by 23.0%. Nocturia was the most commonly reported symptom (35.4%), followed by frequency (25.6%) and urgency (25.3%). Stress urinary incontinence (SUI) was reported by 20.8% of women. Interestingly, nocturia and frequency were generally perceived as less troublesome, with only a minority rating them as problematic. In contrast, urinary incontinence (UI) was frequently reported as highly bothersome, with SUI and urge urinary incontinence (UUI) accounting for significant proportions. Vaginal delivery (VD) and forceps delivery (FD) were identified as significant predictors of LUTS, with statistical significance observed (P < 0.05). Specifically, women who underwent VD, particularly FD, exhibited lower surface electromyography (sEMG) activity compared to those who had cesarean section (CS), both in terms of resting baseline and contraction amplitude (P < 0.001).ConclusionsOver half of the examined women exhibited LUTS 6 weeks postpartum, with the most common symptoms being nocturia, frequency, urgency, and SUI. Straining and urinary incontinence were commonly reported as significantly uncomfortable, particularly severe in cases of UI. Additionally, vaginal delivery methods, especially those involving the use of forceps (FD), seemed to be more likely to cause pelvic floor muscle or nerve damage, making it the key predictor of storage-related LUTS.